The Effect of Zikr Meditation on Post Operative Pain Among Women Post Cesarean Section - Shinta Novelia; Milla Evelianti Saputri; Ficky Adi Putri Sinkawati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Pain is the most common adverse effects in the early postoperative period. Routine pharmacologic Methods may impair the recovery of patients for their sedative and emetic effects. Therefore, patients’ relaxation is necessary for a successful post-operative pain managements and it is among the interventions addressed to improve physiologic response. The aim of this study was to examine the effects of zikr meditation on post-operative pain among post cesarean section women. This is a quasy experimental research with control group pre-test post-test. A total of 30 muslim post cesarean section women were included in the study. Medical information form, Numeric Rating Scale, and Interument Guideline are used to collect the data. The results show that there is a significant difference of pain between experiment and control group (p= .012), there is a significant difference of pain before and after intervention in the experiment group (p= .00).